Analysis of 2G and 4G Network Quality in Solok City - Septima, Uzma; Candra, Dikky; Vitria, Rikki; Alfarezi, Muhammad; Yolanda, Amelia (Brilliance: Research of Artificial Intelligence, 2024)
Gunung Talang, Twin Lake, Gumanti Valley, Hiliran Gumanti and Pantai Cermin sub-districts in Solok Regency, which are dominated by hills and trees, are the cause of unstable signal quality, causing complaints from the public regarding this. So this study is to determine the network quality in Gunung Talang District, Twin Lakes, Gumanti Valley, Hiliran Gumanti, and Pantai Cermin on Telkomsel, XL and Indosat Operators. Checking is carried out using the drive test method  using TEMS Pocket on 2G and 4G networks. The quality of the 2G network from the measurement results was obtained for RxLevel all operators was bad and for RxQual was good except for Telkomsel operators.Meanwhile,on the 4G network, measurement results for RSRP and SINR for all operators are bad. Some areas that have problems are recommended for optimization, site passenger  and site addition. All of this happens because  of obstacles in the form of hills, cliffs, and tall trees at some point. From the results of the study, the quality of the Telkomsel operator's 4G network has an RSRP value of 46.16% and SINR of 61.06%. XL operators have an RSRP value of 42.7% and SINR which is 60.74%.Meanwhile, Indosat Ooredoo has an RSRP value of 43.2% and SINR of 74.6%. As for the 2G network, the quality of Telkomsel's 2G network operator has an RxLevel value of 47.8% and RxQual of 89.49%. XL operators have an RxLevel value of 58.34% and RxQual of 77.62%.Meanwhile,Indosat Ooredoo has an RxLevel value of 46.16% and RxQual is 80.56%.